The Implementation of Jigsaw Learning Model in Teaching Speaking for Senior High School Students - Rohmawati, Putri; Haryanto, Haryanto (Center of Language and Cultural Studies [CLCS], 2021)
Speaking skill is one of the most important skills to acquire foreign or second language learning. This research aimed to describe the concept of speaking skills, the implementation of the jigsaw learning model in teaching speaking, the advantage and disadvantages of the jigsaw learning model, and the strategies to implement the jigsaw learning model in speaking class. The type of this research is descriptive qualitative. It used library research to collect the data. The approach was taken by examining some library materials, publications of research results, and opinions of world leaders, who studied the use of the jigsaw learning model in teaching speaking. Data is in the form of books, journals, encyclopedias, magazines, papers, and articles. The Internet site access method (Website) is applied by browsing websites/sites that provide various data and information related to research, various theories, and practices that the author was researching. The collected data was then checked for correctness, suitability, and reliability through content analysis, then described, and interpreted to conclude. The results of the study showed that the use of the jigsaw learning model was very useful and can improve students' speaking skills. The students become more active in the learning process and have good interaction and communication with other students in the class.